A self-adaptive IoT architecture to support computational resource allocation in an e-health environment Extended Abstract – CTDSI/2025 - Nascimento, Mateus G. do; David, José Maria N.; Dantas, Mario A. R. (Anais Estendidos do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2025)
Intelligent environments are complex interaction spaces between people, sensors, devices, and systems. Software Engineering must tackle the intrinsic characteristics of devices and sensors and complex interactions in intelligent environments to consolidate development practices. This work aims to present a self-adaptive IoT architecture in an intelligent environment and evaluate an information system developed based on the architecture. The proposal concerns how the architecture modules work to develop new information systems. The work was developed through a real-world case study in an intelligent e-health environment. The results showed how a self-adaptive architecture using artificial intelligence can support the development of an information system to manage intelligent e-health spaces.